Analisis Penguatan Karakter Dalam Implementasi Kurikulum Berbasis Cinta (KBC) - Lingga Fahrurrosi; Vina Lailatul Maskuro; Muhammad Zaironi (STIT Al-Ittihadiyah Labuhanbatu Utara, 2026)
The world of education is currently facing a moral crisis in the form of degradation of human values, individualism, and bullying due to an education system that tends to be oriented solely on cognitive achievement. This dehumanization phenomenon demands a curriculum transformation that can integrate spiritual, emotional, and social dimensions holistically. This study aims to comprehensively analyze the implementation of character strengthening in the Love-Based Curriculum (KBC) and map the advantages and limitations of this model in the context of Islamic education. This study uses a library research method with a qualitative content analysis approach through the stages of decontextualization and recontextualization of academic literature and official documents for the 2021–2025 period. The results show that KBC strengthens students' character through internalizing the value of love in three main dimensions: the Source of Love (God and the Prophet), the Sign of Love (knowledge and the environment), and the Rope of Love (self, others, and the homeland). This implementation is supported by operational strategies that include experiential learning, deep learning, compassionate communication, and process-based evaluation. KBC has been proven effective in increasing emotional stability, empathy, and positive behavior in students. Its implementation has positioned character education as a central axis of humanistic-transformative learning. However, its effectiveness is still hampered by limited teaching materials, high administrative burdens on teachers, and uneven training for educators.